SUPRACHOROIDAL HAEMORRHAGE CAUSED BY VALSALVA MANEUVER DURING VITRECTOMY - Rahma, Nur Ainun; Sembiring, Sindy Br; Silitonga, Andrea Radotma; Bangun, Christina YY (Indonesian Vitreoretinal Society, 2025)
Introduction: Suprachoroidal hemorrhage is a rare but significant complication that can occur during intraocular surgery due to valsalva maneuver while patient awake. A rapid blood accumulation in the suprachoroidal space due to increased tension such as valsalva manuever can caused by rupture of the posterior ciliary arteries or vortex veins. Case report : A 43-year-old man with drop IOL following eventful cataract surgery underwent vitrectomy, IOL explantation and iris claw IOL implantation under general anesthesia. After core vitrectomy and IOL explantation the patient suddenly awake. Iris claw IOL implantation was proceed. At the end of surgery massive suprachoroidal hemorrhage was found. One day postoperative the visual acuity was hand movement. Suprachoroidal and vitreous hemorrhage were observed. Oral and topical steroid were administered. Three months post operative the visual acuity 20/50 and residual suprachoroidal hemorrhage was observed. Discussion: Suprachoroidal Hemorrhage incidence during intraoperative is not known because it occurs very rarely. Our case highlights the Valsalva maneuver event during vitrectomy which cause sudden suprachoroidal hemorrhage. Conclusions: Valsava maneuver during vitrectomy could cause a devastating complication such as suprachoroidal hemorrhage. Although it is one of the reversible complications of anesthesia awareness during vitrectomy, it can be resulted severe visual impairment.